A proposal of an updated classification for pelvic relapses of rectal cancer to guide surgical decision‐making. Issue 2 (18th May 2020) - Belli, Filiberto; Sorrentino, Luca; Gallino, Gianfrancesco; Gronchi, Alessandro; Scaramuzza, Davide; Valvo, Francesca; Cattaneo, Laura; Cosimelli, Maurizio
Abstract: Background and Objectives: Selection of patients affected by pelvic recurrence of rectal cancer (PRRC) who are likely to achieve a R0 resection is mandatory. The aim of this study was to propose a classification for PRRC to predict both radical surgery and disease‐free survival (DFS). Methods: PRRC patients treated at the National Cancer Institute of Milan (Italy) were included in the study. PRRC were classified as S1, if located centrally (S1a‐S1b) or anteriorly (S1c) within the pelvis; S2, in case of sacral involvement below (S2a) or above (S2b) the second sacral vertebra; S3, in case of lateral pelvic involvement. Results: Of 280 reviewed PRRC patients, 152 (54.3%) were evaluated for curative surgery. The strongest predictor of R+ resection was the S3 category (OR, 6.37; P = .011). Abdominosacral resection ( P = .012), anterior exenteration ( P = .012) and extended rectal re‐excision ( P = .003) were predictive of R0 resection. S3 category was highly predictive of poor DFS (HR 2.53; P = .038). DFS was significantly improved after R0 surgery for S1 ( P < .0001) and S2 ( P = .015) patients but not for S3 cases ( P = .525). Conclusions: The proposed classification allows selection of subjects candidates to curative surgery, emphasizing that lateral pelvic involvement is the main predictor of R+ resection and independently affects the DFS.